2019
DOI: 10.2478/sdj-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators of dental health care in Serbia

Abstract: Summary Health care has witnessed considerable progresses toward quality improvement over the past two decades. More precisely, there have been global efforts aimed to improve this aspect of health care along with experts and decision-makers reaching the consensus that quality is one of the most significant dimensions and features of health system. Quality health care implies highly efficient resource use in order to meet patient’s needs in terms of prevention and treatment. Quality health care is provided in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…There has been a necessity to assess the quality of communication in dental settings. This is carried out by patient satisfaction surveys which role is to measure and monitor patient satisfaction with dental services in primary care institutions, which was first introduced in Serbia in 2010 by distributing a questionnaire that evaluates whether a dentist provides clear explanations of procedures, among other factors contributing to providing quality health care [19]. This is in accordance with the fact that being able to provide proper and comprehensive information is of utter importance in doctor/ dentist-patient relationship [35].…”
Section: Communication In Dental Medicinementioning
confidence: 99%
See 3 more Smart Citations
“…There has been a necessity to assess the quality of communication in dental settings. This is carried out by patient satisfaction surveys which role is to measure and monitor patient satisfaction with dental services in primary care institutions, which was first introduced in Serbia in 2010 by distributing a questionnaire that evaluates whether a dentist provides clear explanations of procedures, among other factors contributing to providing quality health care [19]. This is in accordance with the fact that being able to provide proper and comprehensive information is of utter importance in doctor/ dentist-patient relationship [35].…”
Section: Communication In Dental Medicinementioning
confidence: 99%
“…However, praxis literature has insisted on introducing a more patient-centred model that would help doctors reach more precise diagnoses, treat their patients more successfully and achieve better overall results [13]. Nowadays, patient-centredness is recognized as one of the essential constituents of continuous quality improvement (CQI) [19]. Fortin et al suggested the socalled biopsychosociological model that respects patients' needs and promotes changing of some important health and lifestyle habits [20].…”
Section: Medical Encountermentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from Monmonier [1], several other authors mention that cylindrical and azimuthal projections can be interpreted as limiting cases of conic projections [3][4][5][6][7][8][9][10][11]. However, there are few attempts to prove this claim [2,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%